2020
DOI: 10.1098/rstb.2019.0513
|View full text |Cite
|
Sign up to set email alerts
|

The fingerprint of the summer 2018 drought in Europe on ground-based atmospheric CO2measurements

Abstract: During the summer of 2018, a widespread drought developed over Northern and Central Europe. The increase in temperature and the reduction of soil moisture have influenced carbon dioxide (CO 2 ) exchange between the atmosphere and terrestrial ecosystems in various ways, such as a reduction of photosynthesis, changes in ecosystem respiration, or allowing more frequent fires. In this study, we characterize the resulting perturbation of the atmospheric CO 2 seasonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 48 publications
2
39
0
Order By: Relevance
“…In this special issue, we provide a synthesis of studies ranging from in situ to continental scales, from in situ monitoring to large-scale remote sensing and to atmospheric and surface modelling to address these questions. Based on dense atmospheric CO 2 mole fraction measurements in Europe, Ramonet et al [38] show that CO 2 concentrations were above the previous years' values during July and August over most of Europe, especially in Central Europe and Scandinavia, but they also point to lower CO 2 mole fractions during spring (May and June). These measurements have large surface flux sensitivity footprints [39] and suggest an increased spring CO 2 sink, followed by a reduction of this sink in summer.…”
Section: Ecological Perspectivementioning
confidence: 97%
“…In this special issue, we provide a synthesis of studies ranging from in situ to continental scales, from in situ monitoring to large-scale remote sensing and to atmospheric and surface modelling to address these questions. Based on dense atmospheric CO 2 mole fraction measurements in Europe, Ramonet et al [38] show that CO 2 concentrations were above the previous years' values during July and August over most of Europe, especially in Central Europe and Scandinavia, but they also point to lower CO 2 mole fractions during spring (May and June). These measurements have large surface flux sensitivity footprints [39] and suggest an increased spring CO 2 sink, followed by a reduction of this sink in summer.…”
Section: Ecological Perspectivementioning
confidence: 97%
“…For the 90day application, we concentrate on the extended summer growing season (April-October) to examine the capacities of the methodology in detecting large-scale terrestrial biosphere anomalies. We focus in particular on the summer of 2018, which saw a spate of intense droughts and heat waves across Central and Northern Europe that altered continent-wide GPP and CO2 storage and flux patterns (Lindroth et al, 2020;Ramonet et al, 2020;Rinne et al, 2020;Wang et al, 2020). Table 2 summarizes the results of the SSA extraction for the ten sites for the period 1 November 2015 to 31 March 2020.…”
Section: Synoptic and Seasonal Anomaly Detectionmentioning
confidence: 99%
“…Figure 8 shows the 90-day extraction procedure at each of the ten sites and is analogous to Fig. 4, except that we show the period 1 January 2018 to 1 January 2019, as we wish to assess the algorithm's performance with regard to the timing, intensity and extent of the 2018 drought and heat wave events across Central and Northern Europe (Ramonet et al, 2020). Figure 9 https://doi.org/10.5194/amt-2021-16 Preprint.…”
Section: Station Total Ssas (Positive Negative)mentioning
confidence: 99%
“…Greenhouse gas (CO 2 , CH 4 , N 2 O, and SF 6 ) measurements in November 2000 were part of the SNO-RAMCES/ICOS-France French monitoring program (Broquet et al, 2013;Lopez et al, 2015;Ramonet et al, 2010;Sturm et al, 2005). Three types of analyzers were used: non-dispersive infrared instruments (NDIR, LICOR-6251 from 7 November 2000 to 20 November 2007; LICOR-6252 from 21 November 2007 to 3 April 2011); gas chromatography (GC, Agilent HP-6890N from July 2010 to April 2015); and cavity ringdown spectrometers (CRDS) commercialized by PICARRO (G1301/no.…”
Section: Greenhouse Gasesmentioning
confidence: 99%
“…Radionuclide measurements are used to determine the boundary layer/free tropospheric conditions (Farah et al, 2018). The CO 2 surface fluxes are estimated and revealed a clear seasonal cycle, under the influence of plant assimilation, and burning of fossil fuel (Lopez et al, 2015;Ramonet et al, 2020). According to Lopez et al (2015), the measurements observed at PUY during the night are representative of the central part of France, mostly west of the station.…”
Section: Trace Gasesmentioning
confidence: 99%